Bullying is Never Ending: Construction of Reporting on Cases of Bullying in Schools: Framing Analysis on Local Mainstream Media - Winda Hardyanti (Jurnal Komunikasi dan Bisnis, 2023)
The case of bullying that occurred at SMPN 16 Malang and affected MS became a topic of discussion in various media, including online media. In reporting a case, media is a reality construct. A number of pros and cons become interesting perspectives raised in the media, including radarmalang.jawapos.com. This study aims to find out how the reporting construction is on news content related to the bullying case that occurred on MS student at SMP 16 Surabaya using the framing analysis method according to Zhongdan Pan & Konsicki. The research results mention that the news construction made by radarmalang.jawapos.com tends to take the side of the government and related institutions and the media tends to bully the school. This is proven by the five news analyzed, none of which highlights the clarification or defense from the school. Radar Malang tends to raise topics that blame the school and the authorities (government, education, culture and arts department, KPAI) framed as if washing their hands of this case. The images selected to accompany the journalism news also tend to put the school in a corner. Radar Malang also tends to overly protect the perpetrators of bullying acts with more subtle diction choices.